Study on Knowledge, Decision Making and Acceptance of Human Papilloma Virus Vaccination among Parents of Primary School Students in Kota Bharu - Mohd Sopian, Mastura; Shaaban, Juwita; Mohd Yusoff, Siti Suhaila; Wan Mohammad, Wan Mohd Zahiruddin (2015)
NTRODUCTION: Cervical cancer is the third most common cancer in women and fifth most common cancer in the entire general population in Malaysia 1. The primary prevention, HPV vaccine is only approved for use in females in Malaysia2. Children rely on parents not only for the consent even for the guidance and information about the vaccines3. OBJECTIVES: The study to determine the level of parental knowledge, decision making and acceptance of HPV vaccination, and association between knowledge and acceptance. METHODS: This cross sectional study was conducted among 280 parents of primary school students in Kota Bharu for 12 months duration. Systemic random sampling and a validated self administered questionnaire was used to assess knowledge of HPV vaccination. Data was analysed using SPSS ver 22. RESULTS: Parents with good knowledge in Kota Bharu was 38% and 62% was poor. Most decision regarding vaccination was a shared decision, 72%. The proportion of acceptance of HPV vaccine for girls was 63%. Level of knowledge (good) has significant association with acceptance of HPV vaccine (95% CI 7.319,36.403, p<0.001). CONCLUSION :Parent’s level of knowledge is low despite the implementation of the HPV vaccine since 2010. Vaccine acceptance is dependent on the level of knowledge. Parents play an important role in determining the success of HPV vaccine program4. The trend of decision making has changed in Malaysian family as most couples make joint decisions in allowing vaccinations on their child as compared to traditionally decision making by father5. KEYWORDS: HPV vaccine, knowledge, decision making, acceptance, parents